The other dream team [videorecording (DVD)] - Markevicius, Marius; Markevicius, Marius; Markevicius, Marius (Lionsgate, 2013)
Everyone knows Magic Johnson, Michael Jordan of the 1992 American Olympic Dream Team. This is the story of the Other Dream Team. They didn't bring their country the gold medal, they brought something much more valuable. After leading the USSR to a gold medal (and victory over the USA) at the 1988 Olympics in Seoul, Sarunas Marciulionis and Arvydas Sabonis were poster boys for the Soviet sports machine. Four years later, after the fall of the Soviet Union, they emerged as symbols of democracy.